Experimental Investigation of the Continuous Transition of Flame-Spreading near the Blow-Off Limit. (19th February 2020) - Komizu, K.; Saito, Y.; Tsuji, A.; Nagata, H.
Abstract : This study investigates the continuous transition from flame-spreading to stabilized combustion near the blow-off limit in opposed forced flow by using expanding solid fuel duct that makes distribution of oxidizer velocity in the axial direction. The stabilized combustion is a diffusion flame that appears in the Axial-Injection End-Burning Hybrid Rocket. The boundary between flame-spreading and stabilized combustion has not been investigated in detail. Polymethyl methacrylate (PMMA) rectangular ducts were used as a fuel, and gaseous oxygen was used as an oxidizer. All firing tests were conducted at atmospheric pressure. The diffusion flame traveled in the opposed-flow field where the oxidizer velocity increases continuously in the upstream direction. The combustion mode changed when oxidizer velocity at the flame tip exceeded a certain value. The oxidizer velocity used in this experiment ranges from 0.6 to 32.8 m/s. Experimental results show that a threshold oxidizer velocity of the transition can be determined. In this study, the threshold velocity was 26.4 m/s.